Pengaruh Isu Kekerasan Dalam Rumah Tangga (KDRT) Terhadap Kesiapan Perempuan Untuk Menikah : Studi Kasus : Mahasiswa Program Studi Ilmu Politik Universitas Sumatera Utara - Jesica Br Barus; Amalia Annisa (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Violence, especially domestic violence, is a violation of human rights and a crime against human dignity and is a form of discrimination. Violence in any form and committed for any reason is a form of crime that cannot be justified. Recently, cases of domestic violence have often occurred and spread in various media. Of course this affects the mindset of women in their readiness to get married and build a household. The purpose of this study will look at the effect of the issue of domestic violence on women's readiness to get married. The research method used is qualitative with a descriptive approach. Researchers will make observations about the influence of the issue of domestic violence on women's readiness to get married, supported by data collected through questionnaires distributed online. The results of this study are